Health Assessment of the Lower Reaches of Longhe River under Watershed Systematic Treatment - YU Binjing; FU Yicheng (Renmin Zhujiang)
River health assessment is the basis for watershed planning,systematic treatment,and ecological restoration.The lower reaches of the Longhe River in Langfang suffer fragile ecology and lack water fluidity,showing a poor water environment.To accurately assess the ecological health of rivers severely disturbed by human activities and identify the fragility factors in the ecosystem,we construct a health assessment index system for the Longhe River based on the analytic hierarchy process (AHP).The river health assessment index system consists of five aspects:hydrological integrity,physical structural integrity,chemical integrity,biological integrity,and social function integrity.The Langfang section of Longhe River is generally in a healthy state with a health assessment score of 75.18.According to the assessment results,the Longhe River watershed has problems such as large development and utilization of water resources,low wetland retention rate,serious artificial disturbance in the riparian zone,and poor quality of the upstream water.The proposed assessment method could provide a reference for the health assessment of rivers under severe artificial control.